Study the Mix Culture and Wild Strain Sp. of Microalgae in Highly Concentrated Municipal Waste Water - Nadzirah, Sha'ari (2013)
Municipal wastewater is one of the major concerns of the environmental problems. The wastewater is contaminated, so the treatment is essential to minimize its effect to nature before it discharge. Wastewater could used as media in biodiesel production has a potential source of low-cost lipids production. The objectives of this study is to identify the nutrient removal efficiency and lipid production by mixed algae culture and wild strain sp. in concentrated municipal wastewater (centrate). All these experiment will be conducted in batch operation to monitor the biomass cultivation for biodiesel production. From this study, the mixed culture of freshwater algae could remove chemical oxygen demand (COD), ammoniacal nitrogen and total phosphorus by 74.5%, 90.9% and 94.2 % respectively from raw centrate and produced 14.8% of dry biomass lipid content much higher value from other sample which is wild strain sp. of freshwater microalgae.